Ekonomia i etyka. Inspiracje konfucjańskie - Sójka, Jacek (Człowiek i Społeczeństwo, 2018)
Ekonomia i etyka. Inspiracje konfucjańskie [Economics and ethics. Confucian inspirations] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 43–66, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The aim of this article is to assess what kind of possible inspirations for economic thinking one can expect from Confucianism. A direct challenge was issued by the work of Kazimierz Poznański who claims that Confucianism is a source of a new paradigm for economics, the one based on ethics. So the question posed in this paper is, to what extent Confucian economics, as presented by Poznański, can become an alternative view counterposed to the western liberal economics, allegedly devoid of ethical contents. To answer that question one should first analyse the relation between economics and ethics within traditional, western, liberal approach. The author of this article posits that ethical component is present within this approach and, at the same time, Confucian values are not that different as far as the goals of economic life are concerned. What is more, one can find some conceptual affinities between Confucius and Adam Smith.